Host migration strategy is shaped by forms of parasite transmission and infection cost. Issue 10 (8th July 2019) - Shaw, Allison K.; Craft, Meggan E.; Zuk, Marlene; Binning, Sandra A.
Abstract: Most studies on the evolution of migration focus on food, mates and/or climate as factors influencing these movements, whereas negative species interactions such as predators, parasites and pathogens are often ignored. Although infection and its associated costs clearly have the potential to influence migration, thoroughly studying these interactions is challenging without a solid theoretical framework from which to develop testable predictions in natural systems. Here, we aim to understand when parasites favour the evolution of migration. We develop a general model which enables us to explore a broad range of biological conditions and to capture population and infection dynamics over both ecological and evolutionary time‐scales. We show that when migration evolves depends on whether the costs of migration and infection are paid in reduced fecundity or survival. Also important are the parasite transmission mode and spatiotemporal dynamics of infection and recovery (if it occurs). Finally, we find that partial migration (where only a fraction of the population migrates) can evolve but only when parasite transmission is density‐dependent. Our results highlight the critical, if overlooked, role of parasites in shaping long‐distance movement patterns, and suggest that infection should be considered alongside more traditional drivers of migration in both empirical and theoretical studies. Abstract : Parasites are rarely considered as a driver of seasonal migration. Here, the authors show how parasite transmission mode, spatiotemporal dynamics of infection and recovery, and the cost currency of infection all shape when host migration evolves. The results highlight the critical role of parasites in shaping long‐distance movement patterns.